Visible Goiter among Pregnant Women Attending Antenatal Clinic in Public Health Facilities of Debre Markos Town, East Gojjam, North West Ethiopia - Yihun Endalamaw; Haji Kedir; Tadesse Alemayehu (Journal of Nutrition and Metabolism)
Background. Goiter is an abnormal enlargement of the thyroid gland due to inadequate intake of iodine and goitrogenic food. It is the most important public health problem in developing countries like Ethiopia and specifically in East Gojjam. Though there are studies on goiter in Ethiopia, the magnitude is not well known and documented in Debre Markos town on pregnant women. Therefore, this study was carried out to assess the magnitude of visible goiter and associated factors among pregnant women visiting antenatal clinic in three public health facilities of Debre Markos town, North West Ethiopia. Methods. Facility-based cross-sectional study was conducted on 401 pregnant women visiting antenatal clinics at three public health facilities using the systematic sampling technique. Data were collected using pretested structured questionnaire by an interview method. All pregnant women were examined for the presence of goiter using World Health Organization (WHO) criteria. Both bivariate and multivariable binary logistic regression analyses were used to see the association between dependent and each independent variable. Result. The prevalence of visible goiter was found to be 10.5% (95% CI: 7.5–13.5). Visible goiter was more common in the age category between 15 and 19 years. Low household income (AOR = 4.5, 95% CI: 1.1–18.7), cabbage intake (AOR = 5.2, 95% CI: 1.2–22.3), and poor knowledge about the benefits of iodized salt (AOR = 2.4, 95% CI: 1.1, 5.2) were factors associated with visible goiter. Conclusion and Recommendation. Visible goiter is a major public health problem in this study area. Low socioeconomic status, low knowledge of pregnant women about the merits of iodized salt, and frequent intake of goitrogenic foods such as cabbage increase the risk of developing visible goiter. Therefore, due emphasis on goiter prevention and control strategies, increasing knowledge of women on the benefit of iodized salt, including low-income households in safety net programs, and nutritional education on iodine-rich diets (such as tuna, dairy products, and egg) should be emphasized to alleviate the problem.